Irregular telomeres impair meiotic synapsis and recombination in mice - Liu, Lin (National Academy of Sciences, 2004)
Telomere shortening can lead to chromosome instability, replicative senescence, and apoptosis in both somatic and male germ cells. To study roles for mammalian telomeres in homologous pairing and recombination, we characterized effects of telomere shortening on spermatogenesis and oogenesis in late-generation telomerase-deficient mice. We show that shortened telomeres of late-generation telomerase-deficient mice impair meiotic synapsis and decrease recombination, in particular, in females. In response to telomere shortening, male germ cells mostly undergo apoptosis, whereas female germ cells preferentially arrest in early meiosis, suggesting sexually dimorphic surveillance mechanisms for telomere dysfunction during meiosis in mice. Further, meiocytes of late-generation telomerase-deficient females with shortened telomeres, bred with early-generation males harboring relatively long telomeres, exhibit severely impaired chromosome pairing and synapsis and reduced meiotic recombination. These findings imply that functional telomeres are important in mammalian meiotic synapsis and recombination.